The Influence Of Career Devlopment And Human Resource Planning On The Work Productivity Of Employees At PT Ansaf Inti Resources Negeri Agung Merapi Barat Kabupaten Lahat - Erik Estrada; M Pahlan; Kasinem Kasinem (Universitas Dehasen Bengkulu, 2026)
This study aims to determine how Career Development and Human Resource Planning partially and simultaneously influence Employee Work Productivity at PT Ansaf Inti Resources Negeri Agung Merapi Barat, Lahat Regency. The sample size for this study was 62 respondents. The sampling method used was incidental sampling. This quantitative study employed multiple linear regression analysis, processed using SPSS, resulting in a regression equation . The results of this study indicate a significant effect between Career Development and Employee Work Productivity at PT Ansaf Inti Resources Negeri Agung Merapi Barat, Lahat Regency. The F-test indicates that Career Development and Human Resource Planning simultaneously influence Employee Work Productivity at PT Ansaf Inti Resources Negeri Agung Merapi Barat, Lahat Regency.